Reducing variation in decomposition odour profiling using comprehensive two‐dimensional gas chromatography. Issue 1 (9th December 2014) - Perrault, Katelynn A.; Stefanuto, Pierre‐Hugues; Stuart, Barbara H.; Rai, Tapan; Focant, Jean‐François; Forbes, Shari L.
<x xml:space="preserve">Abstract</x> Challenges in decomposition odour profiling have led to variation in the documented odour profile by different research groups worldwide. Background subtraction and use of controls are important considerations given the variation introduced by decomposition studies conducted in different geographical environments. The collection of volatile organic compounds (VOCs) from soil beneath decomposing remains is challenging due to the high levels of inherent soil VOCs, further confounded by the use of highly sensitive instrumentation. This study presents a method that provides suitable chromatographic resolution for profiling decomposition odour in soil by comprehensive two‐dimensional gas chromatography coupled with time‐of‐flight mass spectrometry using appropriate controls and field blanks. Logarithmic transformation and t‐testing of compounds permitted the generation of a compound list of decomposition VOCs in soil. Principal component analysis demonstrated the improved discrimination between experimental and control soil, verifying the value of the data handling method. Data handling procedures have not been well documented in this field and standardisation would thereby reduce misidentification of VOCs present in the surrounding environment as decomposition byproducts. Uniformity of data handling and instrumental procedures will reduce analytical variation, increasing confidence in the future when investigating the effect of taphonomic variables on the decomposition VOC profile.